How we became human: mimetic theory and the science of evolutionary origins - Antonello, Pierpaolo (Studies in Violence, Mimesis, & Culture, 2015)
From his groundbreaking Violence and the Sacred and Things Hidden since the Foundation of the World, René Girard's mimetic theory is presented as elucidating "the origins of culture." He posits that archaic religion (or "the sacred"), particularly in its dynamics of sacrifice and ritual, is a neglected and major key to unlocking the enigma of "how we became human." French philosopher of science Michel Serres states that Girard's theory provides a Darwinian theory of culture because it "proposes a dynamic, shows an evolution and gives a universal explanation." This major claim has, however, re